Unfoldings: Essays in schekerian theory and analysis - Schachter, Carl; Straus, Joseph N. (Oxford Oxford university press, 1999)
Carl Schachter is, by common consent, one of the world's preeminent music theorists. He is surely the foremost practitioner of the Schenkerian approach to the music of the eighteenth and nineteenth centuries, which focuses on the linear organization of music and frequently dominates discussions of the standard repertoire in university courses and professional journals. Schachter's articles have thus appeared in a variety of periodicals, including some that are obscure or hard to obtain. This volume gathers some of his finest essays, including those on rhythm in tonal music, Schenkerian theory, and text setting, as well as a pair of analytical monographs, on Bach's Fugue in B-flat major from Volume 1 of the Well-Tempered Clavier and Chopin's Fantasy, Op. 49.